Analysis of Inverted-F and Loaded Inverted-F Antennas for 2.4 GHz ISM Band Applications - Karmokar, Debabrata Kumar; Morshed, Khaled Mahbub (Journal of Electrical Engineering, 2011)
This paper addresses the numerical simulations of Inverted-F and loaded inverted-F antennas for improving the performance of 2.4 GHz industrial, scientific and medical (ISM) band applications. The proposed antennas are directly feed by coaxial connector and the antenna arms effectively control the excited resonant modes for the required operation. Total area occupies by the antennas are 15×34 and 17×34 mm² respectively. The antennas contain an incredibly high peak gain of 8.50 and 8.89 dBi with less than 1.13 and 1.29 dBi gain variation within the 10 dB return loss bandwidth. Also, the antennas have return loss bandwidth of 150 (2355 2505 MHz) and 155 MHz (2370 2525 MHz) with peak return loss of -25.72 and -30.96 dB respectively. Index Terms: Inverted-F antenna (IFA); Loaded inverted-F antenna (LIFA); return loss; ISM band. J. Elec. Engg., Instn. Engrs., Bangladesh, 36(II), December 2009: 4-9